Security in Contemporary Processes of Territorialization of Development – an Attempt to Identify the Problem - Łuczyszyn, Tomasz (Bezpieczeństwo we współczesnych procesach terytorializacji rozwoju – próba identyfikacji problemu, 2023)
The issues of territory management indicate that security should be perceived as a state of the system that can be applied both to the area and to situations, both desirable and undesirable. Building territory security is a complex process. It is mainly based on cooperation between local environment entities participating in mutual issues of local economies and, above all, in local development. Therefore, the problem of "territorialization of security" arises, i.e. linking the success of entities ensuring security with the success of the territory and vice versa. The aim of the article is to draw attention to the development of factors influencing the territorialization of not only economic activity, but also to new factors determining the development of the territory, which manifest themselves in the obligation to ensure security.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 56-62
Keywords: territorialization; territorial development; territorial security; terytorializacja; rozwój terytorialny; bezpieczeństwo terytorialne